Surgical anatomy of sigmoid arteries: A systematic review and meta-analysis. Issue 6 (December 2021) - Cirocchi, Roberto; Randolph, Jutsus; Cheruiyot, Isaac; Davies, R. Justin; Wheeler, James; Gioia, Sara; Reznitskii, Pavel; Lancia, Massimo; Carlini, Luigi; Fedeli, Piergiorgio; di Saverio, Salomone; Henry, Brandon Michael
Abstract: Background: The purpose of this systematic review and meta-analysis was to determine the prevalence of the number of sigmoid arteries (SA) and variations in their origins. Methods: A thorough systematic search of literature through February 2020 was conducted on major electronic databases to identify eligible studies. Data were extracted and pooled into a meta-analysis using Metafor package in R. The primary outcome was the variations in the SA origin (according to modified Zebrowski classification), and the secondary outcome was the prevalence of the number of SA. Results: A total of 22 studies (n = 2653 patients) were included. Type 1 modified Zebrowski (separated origins or common trunk of the SA originating from descending recto-sigmoid trunk (DRST)) was the most common origin type of the SA (pooled prevalence estimate (PPE) = 49.67% (95% CI 32. 67- 66.71)), while type 3 (separated origins or common trunk of 1 or 2 SA originating from DRST or superior rectal artery (SRA) and 1 or 2 SA originating from DRST or SRA) was the least common (PPE = 0.18%; 95% CI 0.00–2.82)). Of the Type 1 variants, the not specified (N.S) variant was by far the most prevalent. The number of SA ranged from one to five, with three being the mode (PPE = 42.3%). Conclusion: This is the most comprehensive analysis of arterial vascular anatomy of the sigmoid colon. In light of the highly variable anatomical pattern displayed by the SA, thorough pre-operative knowledge of their anatomy can be crucial in minimizing incidences of iatrogenic injury. Highlights: A total of 22 studies (2653 patients) were included. Type 1 modified Zebrowski was the most common origin type of the sigmoid artery (SA). Type 3 was the least common. The number of SA ranged from one to five, with three being the mode